Influenza Virus A/Beijing/501/2009(H1N1) NS1 Interacts with β-Tubulin and Induces Disruption of the Microtubule Network and Apoptosis on A549 Cells - Han, Xueqing; Li, Zhihui; Chen, Hongjun; Wang, Huiyu; Mei, Lin; Wu, Shaoqiang; Zhang, Tianyi; Liu, Bohua; Lin, Xiangmei (PLOS ONE, 2012)
NS1 of influenza A virus is a key multifunctional protein that plays various roles in regulating viral replication mechanisms, host innate/adaptive immune responses, and cellular signalling pathways. These functions rely on its ability to participate in a multitude of protein-protein and protein-RNA interactions. To gain further insight into the role of NS1, a tandem affinity purification (TAP) method was utilized to find unknown interaction partner of NS1. The protein complexes of NS1 and its interacting partner were purified from A549 cell using TAP-tagged NS1 as bait, and co-purified cellular factors were identified by mass spectrometry (MS). We identified cellular β-tubulin as a novel interaction partner of NS1. The RNA-binding domain of NS1 interacts with β-tubulin through its RNA-binding domain, as judged by a glutathione S-transferase (GST) pull-down assay with the GST-fused functional domains of NS1. Immunofluorescence analysis further revealed that NS1 with β-tubulin co-localized in the nucleus. In addition, the disruption of the microtubule network and apoptosis were also observed on NS1-transfected A549 cells. Our findings suggest that influenza A virus may utilize its NS1 protein to interact with cellular β-tubulin to further disrupt normal cell division and induce apoptosis. Future work will illustrate whether this interaction is uniquely specific to the 2009 pandemic H1N1 virus.